FACTORS ASSOCIATED WITH CHILDBIRTH - RELATED FEAR AMONG SLOVAK WOMEN - Lucia Mazúchová; Zuzana Škodová; Simona Kelčíková; Alena Rabárová (University of Ostrava, 2017)
Aim: Aim of the study was to examine the intensity of childbirth-related fear, its components and relationship with selected variables (age, parity, and delivery history) among pregnant women in Slovakia. Design: The study was designed as a descriptive cross-sectional study. Methods: A cross-sectional study, 156 pregnant women participated in the research (age 29.7 ± 4.73). The Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ, version A) was used to assess the intensity of childbirth-related fear. A short questionnaire of our own design was used to measure the components of child-related fear. Correlation analysis, ANOVA, and linear regression were employed. Results: The average intensity of child-related fear in the research sample was 68.8 (± 11.6), extreme fear was identified among 9.6% of pregnant women. Child-related fear and age were significantly negatively correlated (R = -0.16; p = 0.05). Results of ANOVA showed significant differences in intensity of fear according to delivery history (F = 4.58; p = 0.005). In the linear regression model, parity and delivery history were shown to be significant predictors of fear of childbirth. The most prevalent components of childbirth-related fear were pain (21.2%), prolonged labor (19.2%), and use of forceps or vacuum extraction (17.6%). Conclusion: Being a primipara, or perceiving a previous labor as complicated were significant factors influencing the fear of childbirth in our sample. The identification of the components and related factors of childbirth-related fear is important in planning effective intervention strategies aimed at anxiety prevention during pregnancy, and contributes to improvement in the quality of life of pregnant women. Keywords: content of fear, childbirth-related fear, childbirth-related fear prevention, predictors of childbirth-related fear, pregnant women.